The Effectiveness of Psychological Capital Training on Organizational Socialization and Job Burnout of Khorramabad Education Staff - Fatima Suleiman Nejad Badreh; Mahdi Khanjani; Ali Delavar (Allameh Tabataba'i University Press, 2022)
The aim of this study was to evaluate the effectiveness of psychological capital training on organizational socialization and job burnout of Khorramabad education staff. The research method was quasi-experimental and its design was pre-test-post-test and follow-up with a control group. The statistical population of the study was all education staff in Khorramabad, whose number at the time of the study was about 1534. The statistical sample of the study was 30 people (due to the semi-experimental nature of the study) was selected by purposive sampling and randomly assigned to the experimental and control groups. Data collection tools included Taormina (1994) Organizational Socialization Questionnaire and Maslash et al. (1996). Data analysis was performed by analysis of covariance. The results of analysis of covariance showed that the adjusted means of socialization scores and burnout in the experimental and control groups were significantly different. Sociability (4.391) F = and (0.04) P =; Burnout: F = (29.339) and P = (0.001) which was significant at the level of 0.05. The use of psychological capital training will increase organizational socialization and reduce employee burnout; therefore, psychological capital training can be used to strengthen the organizational sociability behavior of education staff and reduce their burnout.